2014
DOI: 10.1136/bmjopen-2013-004242
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with domestic violence: a cross-sectional survey among women in Jeddah, Saudi Arabia

Abstract: ObjectiveThis study aims to identify the factors associated with domestic violence (DV) among women in Jeddah.DesignCross-sectional survey.SettingOutpatient departments of three tertiary hospitals in Jeddah.ParticipantsConvenience sample of women, aged 15–70 years, at the outpatient and inpatient clinics.InterventionsBetween 15 December 2011 and 30 May 2012, a psychologist and a professional health assistant explained the purpose of the research to participants, who were then asked to fill a 50-item questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
86
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 41 publications
11
86
4
1
Order By: Relevance
“…These findings are consistent with. [8,14] A growing body of literature, [5,[8][9][10][11]13,15,[19][20][21][22] support our findings that low level of education of the participants was significantly associated with DV. Our results showed that more than two-thirds illiterate ones or those having primary education only reported exposure to DV compared to less than half those having university degree.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…These findings are consistent with. [8,14] A growing body of literature, [5,[8][9][10][11]13,15,[19][20][21][22] support our findings that low level of education of the participants was significantly associated with DV. Our results showed that more than two-thirds illiterate ones or those having primary education only reported exposure to DV compared to less than half those having university degree.…”
Section: Discussionsupporting
confidence: 81%
“…This is because financial independency of the woman is supposed to be protective against DV, moreover, these women who were dependent on their husband for their basic demands, usually accept and tolerate the violence committed against them. However, our results are inconsistent, [5,[20][21][22] where economic independency and presence of ownership were linked to DV and not the opposite which may be explained by different socioeconomic context in which these studies were conducted.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In such societies or groups, females may be considered the property either of their parents, or their spouse. Further, women have less access to education [9,25] and thus are more likely to be dependent on males for financial security [25][26][27]. This results in freedom of choice, movement and the ability to exercise autonomy, as understood in twentyfirst century Western societies and health care systems, being severely curtailed.…”
Section: Ethics and Hivst: Issues Of Population Profilementioning
confidence: 99%